Evaluation of the Influence of Fatigue in Preliminary Design of Road Bridges - Set-based design of concrete frame bridges - Johansson, Mattias; Bohlin, Jon (My University, 2021)
The set-based design process differs from the traditional point-based design approach as several designs are produced and evaluated simultaneously, which contributes to a more efficient design phase. In order to study the utilization of this modern design procedure, a design tool was developed which included several evaluation criteria and verification steps. As a continuation of a previous project (Löfgren, 2020), where the original design tool was created, a study for the potential of development with respect to implementation of fatigue assessment was conducted. Thus, in order to optimize the designs generated by the design tool even further, fatigue verification was thereby implemented to the FE-analysis to see if this could be beneficial in a preliminary design phase. A parametric study was conducted in order to identify important aspects in determining the fatigue capacity to the generated bridge designs. Additionally, aspects which are especially important to the fatigue assessment and potentially of interest to choices done prior the design phase was investigated. Furthermore, comparisons between optimized designs based on the initial preliminary designs criteria and the fatigue verification were conducted in order to establish the influence of fatigue to the design tool. The utilization of the design tool was investigated further by analyzing the selection procedure. Additional measures proved to be of interest in order not to miss potential bridge design in the process. Also, the idea of being able to find standardized bridges which could be suitable for multiple situations was investigated further with the aid of the developed design tool. The conducted investigations in this project showed that the implementation of fatigue verification can be beneficial in order to increase the quality of the final design proposals from the design tool. Also, comparisons showed great potential for such a design tool, when making decisions regarding various design parameters
Keywords: frame bridge, set-based design, fatigue, optimization, FE-modelling; parametric design, python, Lambda method, Cumulative Damage method, concrete